Effectiveness of Agriclinics and Agribusiness training programme in Kerala - S. Parimaladevi,; A. Sakeer Husain,; S. Bhaskaran, (Journal of Agricultural Extension Management, 2025)
The Ministry of Agriculture, Government of India, in association with the National Bank for Agriculture and Rural Development (NABARD), Small Farmers Agribusiness Consortium (SFAC) and the National Institute of Agricultural Extension Management (MANAGE) launched a unique programme of "Agriclinics and Agribusiness Centres Scheme" to take better methods of farming to each and every farmer across the country. The Agriclinics and Agribusiness centres scheme aims to tap the expertise available in the large pool of graduates in agriculture and allied sectors. It is expected that the setting up of agriclinics and agribusiness centres by agriculture graduates trained under the scheme will strengthen transfer of technology and extension services